Self-Determined Goals of Male Participants Attending an Intervention Program for Intimate Partner Violence Perpetrators: A Thematic Analysis - Roldán-Pardo, Manuel (International journal of offender therapy and comparative criminology, 2023)
Treatment adherence and motivation to change are among the main challenges in intervention programs for Intimate Partner Violence (IPV) perpetrators. Motivational strategies have shown promising results in increasing the effectiveness of intervention programs for IPV perpetrators. One of these motivational strategies is goal setting. The aim of this study was to analyze and categorize the self-determined goals (n = 204) of 227 male participants attending an intervention program for IPV perpetrators. Findings of the thematic analysis suggested three levels of analysis: 4 core categories, 12 categories, and 35 codes. The four core categories were “interpersonal relationships” (39.7%), “personal resources for daily life” (29.3%), “coping strategies” (27.8%), and “motivation to change” (3.2%). Identifying the main categories of self-determined goals of IPV perpetrators could guide professionals to tailor the intervention to participants’ specific needs and implement evidence-based strategies to strengthen goal attainment and improve treatment outcomes.